Implications of Transnational Adoption Status for Adult Korean Adoptees. Issue 1 (January 2015) - Langrehr, Kimberly J.; Yoon, Eunju; Hacker, Jason; Caudill, Kathy
<x xml:space="preserve">Abstract</x> This study used a consensual qualitative research method to explore the implications of transnational adoption in the lives of 12 adult Korean adoptees. From the analysis, 6 domains emerged: (a) adoption history and preadoptive memories, (b) meaning of adoption, (c) adoptive family dynamics, (d) racism, (e) identity formation, and (f) counseling experiences. Results highlight the need for more awareness surrounding transnational adoption throughout the life span. Additional suggestions concerning research and practice are discussed. Este estudio usó un método de investigación cualitativa consensual para explorar las implicaciones de la adopción transnacional en las vidas de 12 adultos coreanos adoptados. A partir del análisis, surgieron 6 parámetros: (a) la historia de adopción y las memorias preadoptivas, (b) el significado de la adopción, (c) la dinámica de la familia adoptiva, (d) racismo, (e) formación de la identidad, y (f) experiencias en consejería. Los resultados destacan la necesidad de prestar mayor atención a la adopción transnacional a lo largo de toda la vida. Se discuten sugerencias adicionales relacionadas con la investigación y la práctica.